EVALUASI PROGRAM LITERASI ALQUR’AN BERBASIS MODEL CIPP (STUDI SMAN 6 BULUKUMBA SULAWESI SELATAN) - Rostina Rostina; M Ilham Muchtar; Abdul Rahman Getteng (Almeera Education, 2022)
This study aims to describe the results of the evaluation of the implementation of the Qur'an literacy program at SMAN 6 Bulukumba based on the CIPP (Context, Input, Process, and Product) model. This study uses a qualitative descriptive method with subject data sources from the principal, vice principal of student affairs, the Alqur'an literacy team, PAI teachers, and Alqur'an literacy program assistants, using interview, documentation and observation instruments. Data were analyzed using qualitative data analysis techniques. Research results: 1) Context Evaluation; The purpose of implementing the Qur'an literacy program is in accordance with the needs of students and schools, and for the development of the Qur'an literacy program, SMAN 6 Bulukumba has collaborated with related institutions and agencies. 2) Input Evaluation; the implementation of the literacy program in the form of activity planning stages, understanding of teachers and students in program management, availability of infrastructure, was carried out well although it had to be improved in human resources such as the competence of accompanying teachers, utilization of facilities, program preparation, financing of training and program development. 3) Process Evaluation; In the implementation of the Alqur'an literacy program, the time and place have changed due to the Covid-19 Pandemic, the principal has been very good at monitoring although it has not touched funding in the context of program development. 4) Product Evaluation; the implementation of the Alqur'an literacy program shows the suitability of targets and results, changes in students' interest in reading the Qur'an intensively, increases in learning outcomes to read the Qur'an and student achievement in the religious field.